SIFAT KIMIA ULTISOL DAN RESPON JAHE MERAH TERHADAP PEMBERIAN PUPUK KANDANG SAPI DAN ABU BOILER - Noviriani, Selli; Farni, Yulfita; Fuadi, Najla Anwar (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2026)
Ultisol is a type of soil characterized by relatively low fertility, making it commonly utilized for oil palm plantations. In Sungai Muluk Village, oil palm plantations have surpassed their productive phase, necessitating replanting activities. This condition has resulted in decreased household income among local communities. As an alternative strategy, farmers have adopted red ginger cultivation through an intercropping system. However, the implementation of this system is constrained by soil nutrient deficiencies. This study aims to evaluate the application of cattle/cow manure and boiler ash on changes in the chemical properties of Ultisol soil after oil palm replanting, as well as to optimize the growth of red ginger plants during the maximum vegetative phase. This study used a non-factorial randomized block design with six treatment levels, namely A0 (control), A1 (10 tons ha-1 of cow/cattle manure + 5 tons ha-1 of boiler ash), A2 (15 tons ha-1 of cow manure + 5 tons of ha-1 boiler ash), A3 (15 tons ha-1 of cow manure + 10 tons ha-1 of boiler ash), A4 (20 tons ha-1 of cow manure + 10 tons ha-1 of boiler ash), A5 (20 tons ha-1 of cow manure + 15 tons ha-1 of boiler ash). The parameters observed were pH, exchangeable K, total N, plant height, number of leaves, and fresh weight of rhizomes. The results showed that the application of cow manure and boiler ash to Ultisols after oil palm replanting increased pH, exchangeable cations, plant height, number of leaves, and fresh weight of rhizomes. The combination of cow manure and boiler ash at a dose of 20 tons ha-1 of cow manure + 15 tons ha-1 of boiler ash effectively improved the chemical properties of Ultisol and increased the growth of red ginger plants.